Kontribusi Motivasi Belajar dan Pengetahuan Struktur Berita Terhadap Kemampuan Menulis Siswa Kelas VIII MTsN Kamang - Lisa Yuniarti; Harris Effendi Thahar; Ngusman Abdul Manaf (Bahasa, Sastra, dan Pembelajaran, 2015)
Abstract: The background of this research is the problem that is happening in VIII year students if MTsN Kamang. The writer chooses the students ability in writing news because the students get low score, it is 73 (below the KKM). The writer predicts that there is a link between students motivation in studying and students’ knowledge about news structure. The writer does this research describe how big the contribution of studying motivation and structure news in writing news.The population of this is the VIII year students of MTsN Kamang, consists of 120 students. The writer uses analysis desrciptive method. The technic that is used in this research is simple random sampling with 35 students in this research. The research is using some instruments such as questionnaire, optional test which is used to measure the news structure knowledge, and the writing test is used to measure the ability in writing news. Next, the data is processed using product moment formula, double correlation, F test, double regression test to know how the contribution between the variable. According to the result of the research, the writer concludes: (1) the contribution of studying motivation in writing news ability is 6,10%; (2) the contribution of structure news knowledge is 16%; (3) the contribution of studying motivation and structure news knowledge in writing news is 21,16%. Thus, the writer concludes that studying motivation and structure news knowledge give the contribution in VIII year students of MTsN Kamang ability.